From Asymmetrical Relations to Cooperation and Interactional Dynamics within a Work Collective in a Hospital Environment - Halli , djama (El Omda in Linguistics and Discourse Analysis, 2022)
In any social organization, particularly in the medical field, interaction can be regarded as the mechanism through which power is exercised, and as a space for expressing social divisions, conflicts, as well as calls for compromise. In this regard, our study reflects a subtle interplay between asymmetry and cooperation, in which caregivers and patients are inevitably engaged in a shared and continuous interactional dynamic.